Pedagogical Mastery of a Fine Arts Teacher in Conducting Lessons in the Landscape Genre - Aslonov Furqat Botirovich (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article examines the role of the fine arts teacher’s pedagogical mastery in teaching the landscape genre. It analyzes the strategies, techniques, and professional competencies that enable teachers to effectively develop students’ artistic skills, aesthetic perception, and creative thinking. Special attention is given to innovative teaching methods, such as interactive activities, the “flipped classroom” approach, and the use of digital visualization tools, which enhance students’ engagement and facilitate the formation of artistic literacy. The study highlights how a teacher’s expertise and methodological approach contribute to fostering both technical skills and emotional responsiveness in students.